2015
DOI: 10.1111/pme.12823
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Ratings Needed for Valid Pain Assessment in Clinical Trials: Replication and Extension

Abstract: Composite pain intensity scores created from two individual ratings of recalled pain appear to be adequately valid for detecting treatment effects. Moreover, the findings indicate that the selection of the pain intensity domain to use as a primary outcome variable may play a more important role than increasing reliability by obtaining more assessments; specifically, ratings of recalled worst pain may be more valid for detecting treatment effects than ratings of average pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 30 publications
(58 reference statements)
0
24
1
Order By: Relevance
“…The Quality Oncology Practice Initiative highlights the importance of proper pain management strategies by including documentation of pain assessment as part of their quality metrics . In addition, clinicians should always ask about patterns in pain scores (ie, highest pain score, lowest pain score, average pain score in the past week) and response to analgesic regimen so that historical pain over time can be assessed rather than only focusing on the pain present at the time of the evaluation . This may be done through verbal history, pain diaries, or both.…”
Section: Pain Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Quality Oncology Practice Initiative highlights the importance of proper pain management strategies by including documentation of pain assessment as part of their quality metrics . In addition, clinicians should always ask about patterns in pain scores (ie, highest pain score, lowest pain score, average pain score in the past week) and response to analgesic regimen so that historical pain over time can be assessed rather than only focusing on the pain present at the time of the evaluation . This may be done through verbal history, pain diaries, or both.…”
Section: Pain Assessmentmentioning
confidence: 99%
“…57 In addition, clinicians should always ask about patterns in pain scores (ie, highest pain score, lowest pain score, average pain score in the past week) and response to analgesic regimen so that historical pain over time can be assessed rather than only focusing on the pain present at the time of the evaluation. 58 This may be done through verbal history, pain diaries, or both. Most pain that is not related to an oncologic emergency (ie, spinal cord compression, impending fracture, superior vena cava syndrome, etc) can be effectively managed in the ambulatory setting.…”
Section: Pain Assessmentmentioning
confidence: 99%
“…However, because the main outcome of our study was cumulative opioid use, the study was not designed and did not have adequate power to assess differences in postoperative VAS scores between patient groups. Therefore, we decided to analyze the maximum value of pain during cough, i.e., "the worst possible pain" which, as suggested by Jensen et al (2015) is more important than "average pain" for valid assessment of the treatment effect. In the tDCS treated group, maximum VAS pain during cough was significantly lower after the fifth tDCS session on postoperative day 5.…”
mentioning
confidence: 99%
“…The difference between patients' worst level of pain with that of current level of pain and, least level of pain, could be associated with the fact that these intensity measures (least and current) are not as sensitive as worst pain intensity in detecting treatment effects, and authors have been recommending against [51]. A clinical trial in Taiwan also reported no effect of the treatment when the outcome was current level of pain and the average level of pain, instead of worst pain intensity [52].…”
Section: Discussionmentioning
confidence: 99%